Determinação do ponto de colheita do Camu-camu (Myrciaria dubia (HBK) MC Vaugh J por meio de atributo de qualidade e funcionais - Silva, Vanuza Xavier da (2012)
The camu-camu is a native fruit to the Amazon with a great economic, nutritional and functional potential, mainly due to the vitamin C and the total phenolic contents. These compounds have antioxidant and when added to the human diet might prevent and / or help in the treatment of chronic-degenerative diseases. Thus, the objective of this study was to evaluate the physical, chemical, physic-chemical and functional changes during the development cycle of the camu-camu, in order to accurately determine the harvest time of the fruits, based on the intended destination, either for fresh consumption or even for the extraction industrial of functional compounds. It was performed the following determinations: longitudinal and equatorial diameters, fresh mass weight, ethylene and CO2 production, pH, titratable acidity (TA), soluble solids (SS), total and reducing sugars, starch, total and soluble pectins, enzymes pectinmethylesterase (PE) and polygalacturonase (PG), flavonoids, anthocyanins, carotenoids, ascorbic acid, and total phenolic contents, antioxidant activity by ORAC and DPPH methods. The increase in the fresh mass, equatorial and longitudinal diameters were growing up till 81 DAA, observing decrease after this harvest, probably, due the moisture losses. By the evaluation of the CO2 and ethylene production, it was possible to confirm the metabolic behavior non-climacteric to the fruits of camu-camu, where the quality attributes have began to develop in the harvest performed at 81DAA, indicating the beginning of fruit ripening on the plant. The development of camu- camu in natural environment occurred within the period of 102 days, from the full flowering until the fruit ripening on the plants. In this sense, the sensory quality attributes were more pronounced between 95 and 102 DAA, showing 100% red color, increased of SS / TA ratio, with the reduction of the AT and an increase in the SS and reducing sugars in the fruits. Furthermore, there was observed the increase in the activity of the pectolytic enzymes and the consequent increase in the concentration of the soluble pectins, being these parameters favorable to the consumption of fresh fruit. However, the functional compounds such as vitamin C contents and the anthocyanins were more evident at 88 and 102DAA, respectively. The functional compounds were concentrated mainly in the peel, whose fractions showed higher antioxidant activities, mainly in the fruits harvested at 88DAA, showing the vitamin C as a major contributor to this activity.